Energy Level Alignment at Interfaces in Metal Halide Perovskite Solar Cells. Issue 22 (30th July 2018) - Wang, Shenghao; Sakurai, Takeaki; Wen, Weijia; Qi, Yabing
Abstract: The rapid progress of organic–inorganic metal halide perovskite solar cells (PSCs) has attracted broad interest in photovoltaic community. A typical PSC consists of anode/cathode, a perovskite layer as absorber, and carrier transport layer(s) (electron/hole transport layer(s)), which are stacked together, resulting in multi‐interfaces between these layers. Charge extraction and transport in these solar cell devices are strongly influenced by the interfaces and in particular the energy level alignment (ELA). It is the synergy of multiple interfaces and bulk films embedded in the cell architecture that has led to the extraordinary success of PSCs. Here, the authors review the progress of the studies on energy level alignment in PSCs, including several sections: methods for deriving ELA, semiconductor type of perovskite, bottom layer–dependent energy level shift of perovskite, density of states–governed ELA, ELA for specific interfaces, instability‐induced ELA variation, and defects and ion migration–induced ELA variation. Perspective and outlook for precisely determining ELA, designing the device architecture, and fabricating high performance PSCs are discussed. Abstract : Charge extraction and transport in perovskite solar cells (PSCs) are strongly influenced by the interfaces and in particular the energy level alignment (ELA). The recent advances of the research regarding energy level alignment in PSCs are reviewed. Perspective and outlook for precisely determining ELA, designing the device architecture, and fabricating high performance PSCs are discussed.